Nature and Evolution of the Ore-Forming Fluids from Nanmushu Carbonate-Hosted Zn-Pb Deposit in the Mayuan District, Shaanxi Province, Southwest China - Suo-Fei Xiong; Yong-Jun Gong; Shu-Zhen Yao; Chuan-Bo Shen; Xiang Ge; Shao-Yong Jiang (Geofluids)
The Nanmushu carbonate-hosted Zn-Pb deposit is located in the Mayuan district of Shaanxi Province, a newly discovered metallogenic district next to the Sichuan Basin, in the northern margin of the Yangtze Block, which is the largest and the only one that is currently mined in this district. The δ34S values of sulfides are characterized by positive values with a peak around +18‰, and the reduced sulfur may have derived from reduction of SO42- from paleoseawater or evaporitic sulfates that have possibly been leached by basinal brines during mineralization stage. Detailed fluid inclusion study shows two types of fluids in the sphalerite, quartz, dolomite, calcite and barite, that is, aqueous-salt dominant inclusions (type I) and hydrocarbon-bearing inclusions (type II). The Laser Raman spectroscopy study shows occurrence of certain amount of CH4, C4H6, and bitumen. The salinities show similar values around 6 to 12 wt% NaCl equivalent but a decreasing temperature from early to late stages (typically 200° to 320°C in stage I, 180° to 260°C in stage II, and 140° to 180°C in stage III). These features may be related to basinal brines mixing between an external higher salinity CaCl2  ±  MgCl2-rich fluid and a local H2O-NaCl methane-rich fluid.